STRATEGI KAMPANYE PUBLIC RELATIONS TBS FIGHT FOR SISTERHOOD THE BODY SHOP INDONESIA - Kurniawan, Diva Hairiannissa; Sukardani, Puspita Sari (The Commercium, 2022)
The development of digital-based communication makes the role of public relations as an important figure for the company. The Body Shop Indonesia is an example that realizes the importance of public relations that can be able to carry out the basic principles of the company while maintaining its image. Implementation of the basic principles proven by the existence of TBS Fight For Sisterhood campaign. Based on sexual violence cases in Indonesia that increase without any solution, makes The Body Shop Indonesia's public relations team fight for this. In addition, the RUU PKS, which had been drafted for 8 years, was not ratified. In addition, sexual violence which is considered taboo is also an obstacle for The Body Shop Indonesia to be able to create an appropriate strategy so that there are no cons. Therefore, this study aims to find out how The Body Shop Indonesia's public relations campaign strategy in achieving the main goal of urging the ratification of the RUU PKS so it can create a safe space. This research is descriptive qualitative research with case study method and constructivist paradigm. Data was collected through in-depth interview, observation, and documentation. The results of study show that various strategies have been successfully achieved their main goals while getting various positive impacts for brand.